First record of the silver-cheeked toad fish Lagocephalus scleratus (Gmelin, 1789) (Actinopterygii: Tetraodontidae) from Chennai coastal waters, Southeast India - Silambarasan, Krishnan; Sujatha, Krishnamurthy; Sundaramanickam, Arumugam; Rajalakshmi, Elumalai; Joice, Arokia Doss Anitha (Journal of Fisheries, 2017)
The silver-cheeked toad fish, Lagocephalus scleratus, was recorded for the first time on 25 September 2014. Two specimens of this fish species were collected from the by-catch landed by a commercial deep-sea trawler at Kasimedu Fishing Harbour, Chennai coast, Southeast India. The morphometric and meristic characters of the recorded specimens are described and discussed. The specimen was compared with earlier reports.